9 CD8+ T Cells and Clinical Outcomes from the CYTO Reductive Surgery in Kidney Cancer Plus Immunotherapy and Targeted Kinase Inhibition (Cyto-KIK) Trial - Karie Runcie; Calvin Park; Moshe Ornstein; Biren Saraiya; Somnath Tagore; Edridge D’Souza; Benjamin Izar; Eric Singer; Mark Stein (The Oncologist, 2026)
Abstract Background In 2020, CheckMate9ER established cabozantinib (cabo) and nivolumab (nivo) as a first-line treatment regimen for metastatic clear cell renal cell carcinoma (mccRCC). Despite recent therapeutic advancements in mccRCC, only about 10-15% of patients will achieve a complete response (CR) to current first-line therapy. Improved outcomes with neoadjuvant compared to adjuvant immune checkpoint inhibitors has been demonstrated in several tumor types including non-small cell lung cancer and melanoma. Cytoreductive surgery, in addition to providing symptomatic benefit, removes a large site of tumor which may ultimately develop into a site of immune evasion driven by tumor cell-intrinsic factors in the tumor microenvironment. We hypothesized that if tumor specific immune responses to immunotherapy are greatest prior to nephrectomy, then treatment with nivolumab and cabozantinib both prior to and after cytoreductive nephrectomy (CN) would lead to maximal peripheral and intra-tumoral specific immune responses and higher rates of achieving a complete response. Single-nucleus RNA sequencing (snRNA-seq) studies have begun to characterize RCC tumor-immune microenvironments (TMEs) following immunotherapy exposure, identifying putative T/myeloid cell and tumor markers of treatment response and resistance in conjunction with prior bulk RNA-seq signatures of survival. Our correlative, biomarker-rich study design enables evaluation of the tumor immune microenvironment before initiation of current first-line combination therapy and comprehensive analysis of immune changes across the entire tumor following CN, with the goal of defining mechanisms of resistance to combination immunotherapy in mccRCC. Methods This is an open label phase II, single arm, multicenter trial of combination cabo and nivo prior to and after CN in patients with mccRCC. 38 treatment- naïve subjects were enrolled with the primary endpoint of CR rate according to RECIST version 1.1. Subjects received cabo (40mg) daily and nivo (480mg) every 4 weeks for 12 weeks prior to CN. Post-operatively, subjects resumed treatment with cabo and nivo until evidence of disease progression. Fresh tumor specimens were collected pre-treatment and at time of nephrectomy for snRNA sequencing and paired T cell receptor sequencing. Results Between June 2020 and April 2025, 38 patients were enrolled. 71% of subjects were male and 29% were female with median age 64 years at time of enrollment. 74% of patients had IMDC intermediate-risk disease and 26% of patients had IMDC poor-risk disease. All subjects received at least one dose of the study drugs, however, 6 subjects did not complete CN. Out of 35 subjects, 22% experienced a partial response and 77% had stable disease prior to nephrectomy. The ORR was 50% (3CRs, 13 PRs) for 32 subjects post-CN. 6/13 PRs had RECIST responses ≥95%. 2 subjects have been able to discontinue study treatment and remain in near CR or CR after 30 months of follow-up. There were no path CRs reported but 5 subjects experienced near path CRs (> 90% tumor necrosis). From processed snRNA data, we classified 69,989 nuclei into malignant (n = 36,602) and non-malignant (n = 33,387) categories. Among non-malignant cells, we identify T, natural killer, B/plasma, myeloid, fibroblast, endothelial and non-malignant renal parenchymal cell populations. Cabo and nivo was associated with a decreased proportion of tumor-associated macrophages (TAMs) and elevated presence of CD8+ T cells in tumor tissue. Conclusions This phase II trial of cabo and nivo prior to and after CN demonstrates safety and feasibility with the current IO+TKI standard of care in mccRCC. While the CR rate is consistent with prior phase III studies, a few patients have been able to discontinue treatment with durable responses. Correlative analyses demonstrated that combination cabo and nivo was associated with a decreased proportion of tumor-associated macrophages (TAMs) and elevated presence of CD8+ T cells in tumor tissue. Additional snRNA seq and TCR sequencing will be performed to further characterize the TME and potential resistance mechanisms to cabo and nivo.